The genesis of the Bábí-Baháʼí faiths in Shíráz and Fárs - Afnān, Ḥabīb Allāh (Studies in the history of religions, 2008)
The Bábí and Baháʼí Faiths represent two of the most important religious movements of modern times. This book relates the story of the evolution of the Bábí-Baháʼí community, beginning with the birth of its founder, Siyyid ʼAlí-Muhammad, known as the Báb, in 1819 and then traced over the next century and a half in the city of his birth, Shíráz. Its author, Mírzá Habíbuʼlláh Afnán, was himself born in the house of the Báb, reared by the widow of the Báb, who shared with him many stories of the Báb's life, then spent nearly a year with Baháʼuʼlláh in the ʼAkka-Haifa area, and some ten years in close proximity to Baháʼuʼlláh's son ʼAbduʼl-Bahá. He served for the next half century as the hereditary custodian of the house of the Báb, and as such was uniquely qualified to tell the story of the Bábí-Baháʼí Faiths in the city of Shíráz in remarkable and moving detail.